Factors Influencing Changes in the Interior Architecture of Residential Houses in the Heritage Conservation Area of Luang Prabang Old Town - bounpa, mee (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purpose of study were to 1) the level’s opinion of the factors to changes in the interior architecture of residential houses in the Old Town Conservation Area (UA), and 2) the factors affecting architectural changes in residential buildings in the Old Town Conservation Area (UA). The study employed both quantitative and qualitative methods. The samples of this study were total of 135 individuals living in villages within the UA zone of Luang Prabang City, where the concentration of heritage-style residential houses is higher than in other areas. Data were analyzed using mean, standard deviation, multiple regression analysis. The research findings indicated that: 1) The level’s opinions of the factors to changes in the interior architecture of residential houses in the Urban Conservation Area (UA) of Luang Prabang City found that all factors had an average value of medium, meaning that there is moderate agreement, but when considering each sub-factor, it can be seen that they are economic factors, environmental factors, social factors, and regulatory and legal factors. 2) The factors affecting architectural changes in residential buildings in the Urban Architectural Conservation Area (UA), Luang Prabang City found that the Sig. value was lower than the significance level of 0.05. This means that social factors and environmental factors significantly affected changes in the interior architecture of residential houses in the Urban Architectural Conservation Area (UA) in Luang Prabang City. When considering the independent variables that have the power to predict and explain changes in service quality that affect architectural changes in residential buildings in the Old Town Conservation Area (UA) in Luang Prabang, the percentage reached 27.20%.